A Pengujian Vibrasi Pada Pompa Sentrifugal Sebagai Langkah Preventif Untuk Menjaga Stabilitas Kinerja Pompa - DWI LESMANA, DIO; NAHRUDIN IBAD, MUHAMAD; MAHENDRA SAKTI, ARYA (Jurnal Rekayasa Mesin, 2026)
Centrifugal pumps are essential equipment in industrial systems that function to continuously transfer fluids. The reliability and stability of pump performance are strongly influenced by mechanical conditions during operation, particularly in rotating components such as bearings. Mechanical disturbances in pumps are often not visually detectable at an early stage; therefore, an effective condition monitoring method is required. This study aimed to evaluate the performance condition of a centrifugal pump through vibration testing as a preventive maintenance approach. The method used was vibration measurement employing a VibXpert 2 device with vibration velocity parameters based on Root Mean Square (RMS) values. Measurements were conducted at the pump bearings in three directions: vertical, horizontal, and axial. The test results showed vibration values of 0.360 mm/s in the vertical direction, 0.815 mm/s in the horizontal direction, and 0.518 mm/s in the axial direction. All measured vibration values were below the threshold limits specified in the ISO 10816-3 standard for group 2 machines with rigid foundations. Based on these results, it was concluded that the centrifugal pump condition remained within a safe category or new machine condition. Vibration testing was proven to be an effective condition monitoring method to maintain performance stability and prevent early failure in centrifugal pumps.